(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In large numbers of the industrial sectors, wireless networking technologies are acquiring rapid endorsement on account of their cost-adequacy, improved unwavering quality, and adaptability. A wireless network can be characterized as a network of devices, meant as hubs. Their essential usefulness is to corporately detect, accumulate, measure, and distribute data in the general climate. Wireless methods communication without the utilization of wires other than the recieving wire, the Ethernet, and the ground replacing wires. For a few industrial activities, wireless technology bears the cost of savvy and compelling availability arrangements. Utilizing wireless technology there are numerous advantages, for example, distant offices, cycles and field activity which brings about improving productivity, personal time, quicker and more accurate data assortment.